The mediating role of affective commitment with the team in the relationship between trust and innovation in teams with some degree of virtuality - Bastos, Liliana (2019)
Group innovation involves social processes that are facilitated by group trust and affective commitment to the team. The present paper intends to analyze, in a context of teams with some degree of virtuality, the relationship between trust and group innovation, considering the affective commitment with the team as the mediator. To achieve the proposed objective, an empirical study was carried out, with a cross-sectional nature, focusing on 57 work teams from Portuguese organizations pertaining to different sectors of activity. Using surveys as the method in order to collect information, the data was analyzed at the group level, and a simple mediation model was tested. The results revealed a positive and statistically significant relationship between group trust and affective commitment with the team, as well as between affective commitment and group innovation, in the affective trust mediation model. The mediation hypothesis was not supported. These results reinforce the literature that considers the relevance of group trust as a strategy to increase the affective commitment with the team and suggests that this latter may constitute a variable not to be neglected in promoting group innovation.